The Effects of Non-Exclusive Breastfeeding on the Risk of Pneumonia in Children under Five: Meta-Analysis - Putu Anggi Widia Karmany; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2020)
Background: Pneumonia is an inflammation of the lung parenchyma caused by pathogenic microorganisms such as bacteria, viruses, fungi, and parasites that can occur together with lower respiratory tract infections. Pneumonia is the cause of death for more than 800,000 children under five worldwide in 2017. One of the risk factors for pneumonia is a history of breastfeeding (ASI). This study aimed to esti